Neuroendocrine tumour of the lung: a diagnostic challenge / Nur Hidayah Bahrom ... [et al.] - Bahrom, Nur Hidayah; Ramli, Anis Safura; Samsudin, Nor Suraya; Mohamad Ali, Norliana Dalila; Bakar, Nor Salmah (Universiti Teknologi MARA Cawangan Selangor, 2019)
This is a case of a 62-year-old Indian man who was diagnosed with a rare type of lung neuroendocrine tumour (NET) of atypical carcinoid (AC) subtype which comprises only 0.1%- 0.2% of pulmonary neoplasms. He initially presented to a private hospital in May 2018 with a 6-month history of chronic productive cough and haemoptysis. Chest X-Ray (CXR), CT scan, bronchoscopy, biopsy and broncho-alveolar lavage were conducted. At this stage, imaging and histopathological investigations were negative for malignancy. Diagnosis of bronchiectasis was made and he was treated with antibiotic and tranexamic acid. Due to financial difficulties, his care was transferred to a university respiratory clinic in June 2018. His condition was monitored with CXR at every visit and treatment with tranexamic acid was continued for 6 months. However, due to persistent haemoptysis, he presented to the university primary care clinic in Dec 2018. Investigations were repeated in January 2019 where his CXR showed increased opacity of the left retrocardiac region and CT scan revealed a left lower lobe endobronchial mass causing collapse with mediastinal lymphadenopathy suggestive of malignancy. Bronchoscopy, biopsy and histopathology confirmed the presence of NET. Although the Ki-67 index was low, the mitotic count, presence of necrosis and evidence of liver metastases favoured the diagnosis of AC. A positron emission tomography Ga-68 DONATOC scan showed evidence of somatostatin receptor avid known primary malignancy in the lungs with suspicions of liver metastasis. He was subsequently referred to the oncology team and chemotherapy was initiated. This case highlights the challenge in diagnosis and management of patients with AC. Physicians ought to be vigilant and have a high index of suspicion in patients who present with persistent symptoms on multiple visits. Early diagnosis of NET would prevent metastasis and provide better prognosis. Continuous follow-up shared care between primary care and secondary care physicians is also essential to provide ongoing psychosocial support for patients with NET, especially those with metastatic disease.